Entendendo as razões para a recusa da Colecistectomia em indivíduos com Colelitíase: como ajudá-los em sua decisão - Peron, Adilson (2014)
Introduction: Cholelithiasis is very prevalent surgical disease, with approximately 60,000 admissions per year in the Unified Health System in Brazil (Sistema Único de Saúde - SUS). Is often asymptomatic or oligosymptomatic and major complications arise from the migration of calculi to biliary low tract. Despite these complications are severe and life threatening, many patients refuse surgical treatment. Objectives: To understand the reasons why individuals with cholelithiasis refuse cholecystectomy before complications inherent to the presence of gallstones in the bile duct and pancreatitis occur. Methods: To investigate the justifications for refusing to submit to surgery we performed individual interviews according to a predetermined script. In these interviews, we evaluate the degree of knowledge of individuals about the disease and its complications and the reasons for the refusal of surgical treatment. We interviewed 20 individuals with cholelithiasis who refused or postponed surgical treatment without a plausible reason. In these interviews, we apply the thematic analysis (MINAYO, 2006). Results: The majority of participants has good knowledge of their disease and its possible complications, were well oriented and had the right surgical indications by their physicians. The refusal for surgery is based primarily on negative experiences of themselves or family members with surgery, including anesthesia; unexplained fears of surgery and, some, cannot specify the reason for the denial or prefer to get the risk and wait for complications to then have to solve them compulsorily. Conclusions: The reasons for the refusal to surgical resolution of cholelithiasis are diverse, but are closely related to personal negative surgical experiences or related persons or complex problems of psychological nature that must be adequately addressed by the surgeon and other qualified professionals. Our study has the proposal of an informed consent that brings all the information about the surgery, its preoperative and postoperative risks, as well as figures with friendly format intended to inform and to help the patients in their decisions